Wind tunnel as a tool in bird migration research. (10th February 2017) - Hedenström, Anders; Lindström, Åke
Abstract : Wind tunnels, in which birds fly against an artificially generated air flow, have since long been used to evaluate aerodynamic properties of steady bird flight. A new generation of wind tunnels has also allowed the many processes associated with migratory flights to be studied in captivity. We review how wind tunnel studies of aerodynamics and migratory performance together have helped advancing our understanding of bird migration. Current migration theory is based on the power‐speed relationship of flight as well as flight range equations, both of which can be evaluated using birds flying in wind tunnels. In addition, and depending on wind tunnel properties, performance during gliding and climbing flight, and effects of air pressure, humidity and turbulence on bird flight has been measured. Long‐distance migrant species have been flown repeatedly for up to 16 h non‐stop, allowing detailed studies of the energy expenditure, fuel composition, protein turnover, water balance, immunocompetence and stress associated with sustained migratory flights. In addition, wind tunnels allow the fuelling periods between migratory flights to be studied from new angles. We end our review by suggesting several important topics for future wind tunnel studies, ranging from on of the key questions remaining, the efficiency at which chemical power in converted to mechanical power, to new useful avenues, such as improving and calibrating the techniques used for tracking of individual birds in the wild.